а)2sin²x-3sinx-2=0
Замена sinx=t
2t²-3t-2=0
D=3²+4×2×2=25
t₁= 3+√D÷4=3+5÷ 4=8÷4=2
t₂=3-√D÷4=3-5÷4=-2÷4=-0,5
Возвращаемся к замене
sinx=2 sinx=-0,5
решения нет х=(1)⁻k(cтепень)arcsin(-1\2)+πn,n∈Z
-1≤sinx ≥1 x=(1)⁻k × -π\6 +πn,n∈Z
4cos²x+4sinx-1=0
cos²x=1-sin²x
4( 1-sin²x)+4sinx-1=0
4-4sin²x+4sinx-1=0
-4sin²x+4sinx-1+4=0
-4 sin²x+4sinx+3=0 ÷(-1)
4sin²x-4sinx-3=0
Замена sinx=t
4t²-4t-3=0
D=4²+4×4×3=16+48=64
t₁=4+√D÷8= 4+8÷8=12÷8=1,5
t₂=4-√D÷8=4-8÷8= -4÷8=-0,5
Возвращаемся к замене
sinx=1,5 sinx=-1\2
решения нет х=(1)⁻k(cтепень)arcsin(-1\2)+πn,n∈Z
-1≤sinx ≥1 x=(1)⁻k × -π\6 +πn,n∈Z
1)y/y^2-9 - 3/9-y^2 = y /y^2-9 - (-3/y^2-9) = y /y^2-9 + 3/y^2-9 = y+3/(y-3)(y+3)= 1/y-3
2)2x/x^2-4 - 4/4 - x^2 =2x/x^2-4 - (-4/x^2-4) = 2x+4/x^2-4 = 2(x+2)/(x-2)(x+2)= 2/x-2
3)x2/x-7 + 7x/7-x = x^2/x-7 - 7x/x-7 = x^2-7x/x-7 = x(x-7)/x-7= x
4)7/x^2-9x + 3x-7/x^2-9x =7+3x-7/x^2-9x= 3x/x^2-9x
5)5y-19/11y + 6y+8/11y =5y-19+6y+8/11y= 11y - 27/11y
6)y+3/y-3 - 9-y/y-3 =y+3-9-y/y-3=-3/y-3
7)12a+b/28a - b-30a/28a =12a+b-b-30a/28a = -28a/28a = -1
8)6a-4/2 - 2-3a/2 =6a-4-2-3a/2 = 3a+6/2 = 3(a+2)/2
9)b/a-b - a/a-b =-a/a-b - b/a-b = -(a-b)/a-b = -1
10)5a/a-b - 5b/a-b =5a-5b/a-b = 5(a-b)/a-b = 5
11)m^2/m-5 - 25/m-5 =m^2-25/m-5 = (m-5)(m+5)/m-5= m+5
12)a^2-47/a+7 - 2/a+7 =a^2-47-2/a+7 = a^2-49/a+7 = (a-7)(a+7)/a+7=a-7
13)m/m^2-n^2 - n/m^2-n^2 =m-n/m^2-n^2= m-n/(m-n)(m+n)=1/m+n
14)m2/m+n - n^2/m+n =m^2-n^2/m+n = (m-n)(m+n)/m+n = m-n
15)n^2/3n+3m - m^2/3n+3m =n^2-m^2/3n+3m = (n-m)(n+m)/3(n+m) = n-m/3
1+2+5+10=18
1+1+2+2+5+5+10+10=36
1+1+1+2+2+2+5+5+5+10+10+10=54
и т.д. каждая полученная сумма будет на 18 больше предъидущей